Ferritin levels during structured treatment interruption of highly active antiretroviral therapy - José Boom (2018)
Objective: The aim of the study was to investigate the influence of highly active antiretroviral therapy (HAART) on iron status and, conversely, the influence of iron status on the response to HAART. Methods: Ferritin levels were retrospectively determined in stored plasma from 138 HAART-naïve, moderately immunosuppressed HIV-infected Thai patients participating in a structured treatment interruption trial. Ferritin levels were determined at three predefined time-points: (1) HAART initiation; (2) HAART discontinuation; and (3) HAART resumption. Results: At baseline, 31% and 16% of the HIV-infected patients included in the study had high (>200 ng/mL) and low (<30 ng/mL) ferritin levels, respectively. Ninety-five per cent of patients with low ferritin levels were female. Ferritin decreased significantly during the interruption phase of HAART (-8.8ng/mL; P=0.0005) but remained elevated in 62% of the patients with high baseline levels. A low baseline ferritin level was associated with a shorter time (P= 0.041) to reach the CD4 cell target for HAART interruption (350cells/μL), compared with a normal or high baseline ferritin level. Moreover, in a multivariate model, the relative risk (RR) of arriving at this CD4 cell target was significantly higher [RR 1.81; 95% confidence interval (CI) 1.05-3.14] in patients with low baseline ferritin. It is unlikely that inflammation affected ferritin in our patients, as mean levels of C-reactive protein were not elevated in patients with either high or low ferritin levels. Conclusions: Both high and low ferritin levels were highly prevalent in moderately immunosuppressed HIV-positive Thai patients. Structured treatment interruption of HAART resulted in a significant decrease in overall ferritin levels. Furthermore, subjects with low baseline ferritin levels had a faster and greater CD4 response to HAART, suggesting a potential beneficial effect of iron deficiency on immunological recovery after initiation of HAART. © 2007 British HIV Association.